High-strength ultrafine grain Mg-7.4%Al alloy synthesized by consolidation of mechanically alloyed powders - Chaubey A.K.; Scudino S.; Samadi Khoshkhoo M.; Prashanth K.G.; Mukhopadhyay N.K.; Mishra B.K.; Eckert J. (My University, 2025)
Highly-dense ultrafine grain Mg-7.4%Al bulk samples with grain size of about 300 nm have been produced by powder metallurgy through hot consolidation of mechanically alloyed powders. Room temperature compression tests of the consolidated bulk material reveal remarkable mechanical properties: high compressive strength of about 690 MPa combined with a plastic strain exceeding 9%. The high strength of the alloy can be attributed to the combination of three different strengthening mechanisms: grain size refinement, dispersion strengthening and solid solution strengthening. The fracture surface shows trans-granular quasi-cleavage fracture in nature. The MgO rich regions often acted as the microcrack initiation source and thereby stop the main crack. Uniformly distributed intermetallic (γ-Al12Mg17) particles in the matrix deflected main crack and resulted a tortuous crack path. These results demonstrate that powder metallurgy, mechanical alloying combined with hot consolidation is a suitable method for the production of nanostructured Mg-based materials characterized by high strength and considerable plastic deformation. © 2014 Elsevier B.V. All rights reserved.